2021
DOI: 10.3389/fimmu.2021.684657
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Regulatory T Cells in Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a chronic, incurable condition characterized by pulmonary vascular remodeling, perivascular inflammation, and right heart failure. Regulatory T cells (Tregs) stave off autoimmunity, and there is increasing evidence for their compromised activity in the inflammatory milieu of PAH. Abnormal Treg function is strongly correlated with a predisposition to PAH in animals and patients. Athymic Treg-depleted rats treated with SU5416, an agent causing pulmonary vascular injury, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 117 publications
1
22
0
Order By: Relevance
“…These results suggested that the targets of m6A regulators participated in the regulation of the activity of Tregs. According to previous studies, abnormal Treg function was strongly correlated with a predisposition to PAH in animal models and PAH patients ( Tian et al, 2021 ). The present study was the first one to reveal that the m6A regulators in Tregs were abnormal, and the target genes of these m6A regulators were involved in the regulation of the important biological functions of Tregs.…”
Section: Discussionmentioning
confidence: 81%
“…These results suggested that the targets of m6A regulators participated in the regulation of the activity of Tregs. According to previous studies, abnormal Treg function was strongly correlated with a predisposition to PAH in animal models and PAH patients ( Tian et al, 2021 ). The present study was the first one to reveal that the m6A regulators in Tregs were abnormal, and the target genes of these m6A regulators were involved in the regulation of the important biological functions of Tregs.…”
Section: Discussionmentioning
confidence: 81%
“…Restriction and downregulation of immune responses is fundamental to control inflammatory conditions and to sustain self-tolerance and is thus of particular importance in the prevention of autoinflammation and autoimmunity. To date, T regs which secret the anti-inflammatory cytokine IL-10 ( Martini et al, 2020 ; Tian et al, 2021 ) have been studied in the context of various cardiovascular diseases like atherosclerosis ( Meng et al, 2016 ) and also PH where they have beneficial effect in terms of disease progression, implying that T reg deficiency or malfunction might trigger disease aggravation ( Martini et al, 2020 ; Tian et al, 2021 ; Figure 1 ).…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…T-regs modulate immune responses and maintain tolerance to self-antigens 57 . In PAH, T-regs deficiency can lead to unchecked immune responses against self-antigens, resulting in endothelial injury and vascular remodeling 58 . In a preclinical study, T-regs-depleted athymic rats developed severe pulmonary hypertension after exposure to hypoxia 59 .…”
Section: Cytokines and Chemokinesmentioning
confidence: 99%